Life is but a dream - James, Brian, 1976- (Feiwel & Friends, 2012)
When fifteen-year-old Sabrina meets Alec at the Wellness Center where she is being treated for schizophrenia, he tries to persuade her that it is the world that is crazy, not them, and she should defy her doctors rather than lose what makes her creative and special.